Perlindungan Hukum Bagi Pemegang Sertifikat Hak Atas Tanah Dalam Kasus Sertifikat Ganda - Annisa Shafarina Ayuningtyas; Rosita Candrakirana; Fatma Ulfatun Najicha (Jurnal Discretie, 2020)
This study discussing about the factors that causing the emergence of a double certificate and how agrarian law in Indonesia provides legal permission for certificate of land rights holder. This research is a normative legal research that acts prescriptive. The approach that used in this research are case reporting (case approach) and accessing the law (statute approach). Sources of data obtained from primary, secondary and tertiary legal materials. From the research results it is known that the factors of double certificate are inaccuracy of National Land Agency in the process of certificates issuance. Double certificate causes legal uncertainty for holders of land rights, thus potentially causing disputes in the future which also causing loss for both of holders. Legal protection obtained by the holders of land rights that are harmed because of the existence of double certificate are cancellation and revocation of related documents that are considered harmful by National Land Agency.